Rotational atherectomy through the radial artery is associated with similar procedural success when compared with the transfemoral route. Issue 3 (May 2015) - Kotowycz, Mark A.; Khan, Sohail Q.; Freixa, Xavier; Ivanov, Joan; Seidelin, Peter H.; Overgaard, Christopher B.; Džavík, Vladimír
<x xml:space="preserve">Abstract</x> Objectives Rotational atherectomy (RA) has traditionally been carried out using 7 or 8 Fr guides through a transfemoral approach to allow for passage of 2.0 mm burrs or larger. With transradial percutaneous coronary intervention becoming more common, our aim was to investigate whether transradial RA would offer equivalent rates of procedural success when compared with transfemoral RA. Methods Using a prospective percutaneous coronary intervention registry, we identified all patients who had undergone RA at the University Health Network between January 2001 and December 2012 and compared those in whom the transfemoral approach had been used with those in whom the transradial approach had been used. Results A total of 119 patients were analyzed (67 femoral, 52 radial). Larger guides were used in the femoral group compared with the radial group (6.79 vs. 6.31 Fr, P<0.001), but there was no significant difference in the number of burrs used or the average size of the burrs. There was no significant difference in the procedural success rate (91 vs. 96%, P=0.46), fluoroscopy time (40.5 vs. 43.8 min, P=0.37), radiation dose (27743 vs. 29939 cGy cm2, P=0.50), or contrast use (429 vs. 384 ml, P=0.19) between the two groups. Patients in the femoral group were more likely to have a transvenous pacing wire inserted (25 vs. 6%, P=0.006). Access site crossover tended to occur more frequently in the radial group (6 vs. 0%, P=0.08). Conclusion We have shown that RA through the transradial route is associated with outcomes similar to those achieved through the transfemoral route. Keeping in mind the single-center context and the small number of operators, our data do not suggest an increased rate of failure of RA through the radial route despite the use of smaller guiding catheters.